2014
DOI: 10.1021/am500302t
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Anisotropic Gold Nanoparticles for Photothermal Therapy of Cancer

Abstract: Nanoparticles of varying composition, size, shape, and architecture have been explored for use as photothermal agents in the field of cancer nanomedicine. Among them, gold nanoparticles provide a simple platform for thermal ablation owing to its biocompatibility in vivo. However, the synthesis of such gold nanoparticles exhibiting suitable properties for photothermal activity involves cumbersome routes using toxic chemicals as capping agents, which can cause concerns in vivo. Herein, gold nanoparticles, synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 41 publications
2
95
0
Order By: Relevance
“…As shown in Figures and , the morphology of biosynthesized AuNPs was nearly spherical in shape with small size, which was obtained by TEM and SEM analysis. A similar observation was found that spherical size is smaller than other morphologies . Some large images of biosynthesized AuNPs with triangle, pentagon and hexagon shapes were also observed.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figures and , the morphology of biosynthesized AuNPs was nearly spherical in shape with small size, which was obtained by TEM and SEM analysis. A similar observation was found that spherical size is smaller than other morphologies . Some large images of biosynthesized AuNPs with triangle, pentagon and hexagon shapes were also observed.…”
Section: Discussionmentioning
confidence: 99%
“…AuNPs synthesized by green chemistry route using cocoa extract have shown NIR absorbance. The cell death was induced through the photo-thermal ablation of epidermoid carcinoma cells by these AuNPs, facilitating their use as photo-thermal therapeutic agents (Fazal et al 2014).…”
Section: Protein Denaturationmentioning
confidence: 99%
“…Though in the wet chemical methods yielding of nanoparticles is very large but because of cytotoxity of synthetic reagents used like sodium borohydrate,cetrymethyle ammonium bromide (CTAB) it may not bea suitable one for bio analyticalapplication [4].Green synthesis of nano particle has overcome these problems by reducing hazardous and toxic bi-products and become an alternate of syntheticchemicals techniques. Asin greentechnique comprises of different plant parts, biomass and microorganisms etc that is all natural components so very less possibility of formation of toxic bi-products [5]. Among all the bio techniques plant leaf extract is wieldy explored as it is simple, one step, cost effective and ecofriendly and more over phythochemicals present in leaf extract act both as stabilising as well as capping agent [6,7].…”
Section: Introductionmentioning
confidence: 99%